EVANGELIZATION OF CULTURES: A TASK AT HAND - Mascarenhas, Theodore (Asian Horizons, 2011)
The words of Pope Paul VI in the Post synodal Exhortation Evangelii nuntiandi written after the Third General Assembly of the Synod of Bishops devoted to evangelization, was a game changer as far as evangelization was concerned. With this document an entirely new area and a new perspective was introduced into the concept of evangelization.